48.0k views
4 votes
The explicit rule for a sequence is given.

an=3(16)n−1



Enter the recursive rule for the geometric sequence.

a^1=

a^n=

2 Answers

0 votes


a_(1)=3


a_(n)=16a_(n-1)

just use the standart recursive for geometric sequence

User JohnCoene
by
5.6k points
1 vote

Answer:


a_1=3


a_n = 16 \cdot a_(n-1)

Explanation:

The explicit formula for the geometric sequence is given by:


a_n =a_1 \cdot r^(n-1) ....[1]

where


a_1 is the first term

r is the common ratio of the consecutive terms

n is the number of terms

Given that:

The explicit rule for a sequence is given. by:


a_n =3 \cdot (16)^(n-1)

On comparing with equation [1] we have;


a_1=3 and r = 16

Use the recursive formula for the geometric sequence is:


a_n = r \cdot a_(n-1)

Substitute the given values we have;


a_n = 16 \cdot a_(n-1)

therefore, the recursive rule for the geometric sequence is,
a_n = 16 \cdot a_(n-1)

User Clyde Barrow
by
5.5k points